Humor as a multifaceted resource in healthcare: an initial qualitative analysis of perceived functions and conditions of medical assistants’ use of humor in their everyday work and education - Raecke, Julia [Verfasser]; Proyer, René T. [Verfasser] (My University, 2022)
“It has been argued that humor serves as a crucial resource for healthcare professionals (HCPs). For example, they can use it to cope with work stress, to build relationships with patients, and/or to educate medical students and residents - to name but a few functions. However, empirical studies on the importance of humor among HCPs are still scarce. Existing studies primarily focus on nurses and physicians and rarely distinguish between different humor styles (e.g., light and dark). Based on qualitative interviews with 14 German Medical Assistants (MAs), we investigate the potential of humor as a resource for MAs’ work and education. We focus on the perceived functions and conditions of MAs’ successful use of humor as well as the role of humor styles (i.e., comic styles). Results indicate various functions of humor in MAs’ everyday work (e.g., soothing patients, coping with mistakes, fostering team cohesion, or promoting apprentices’ education) as well as different conditions for a successful use of humor (e.g., positive social basis, current well-being, and social sensitivity). Further, the results suggest that the use of a certain humor style depends on the interlocutor as well as the intended goal of the humor. The results not only stress the multifaceted potential as well as the relevance of conditions of successful humor for MAs’ everyday work and education, but also provide valuable real-life insights into MAs’ everyday humor, thus offering several implications for practice to promote humor as a positive resource in MAs.“ (authors’ abstract; BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; 370; 300; Pflegeberuf; Medizinischer Fachangestellter; Humor; Typologie; Einflussfaktor; Berufsausübung